Mental Health and Psychological Well Being as Determinants of Leadership Styles of Political Office Holders in South West, Nigeria: Implication for Good Governance and Sustainable Development - Babalola, Segun O.; Ogunyemi, Ajibola O.; Sadiku, Funmilayo Adeola (NIU Journal of Humanities; Vol 4 No 3 (2019): KIU Journal of Humanities, Vol. 4 No. 3, September 2019, 2019)
Abstract. The study aimed at investigating the influence of psychological well-being and mental health on the leadership styles of political office holders in south-western Nigeria. The expo-factor research design was used. The population comprised all the political office holders in the six states in south-western Nigeria. Stratified random sampling technique was used to select 120 political office holders in south west, Nigeria as the sample. The study adopted three questionnaires, Leadership styles questionnaire, Mental Health Inventory and Psychological well-being questionnaire with good psychometric properties for data collection. Two hypotheses were raised and tested using Factorial logistic regression analysis. Findings revealed that the two predictor variables (Mental health and psychological well-being) individually predicted the criterion variable (Leadership styles at the three levels; authoritarian, democratic and laizess-faire). Sequel to these findings, a number of recommendations were made among which is that there is need for psychologists to move for a bill that will make psychological test as part of the stringent criteria for contesting any election or appointing political leaders into any office in Nigeria. Keywords : Leadership styles, Good Governance , sustainable development, Mental Health, Psychological well-being, Political Office holders.